2021
DOI: 10.1111/jocn.15565
|View full text |Cite
|
Sign up to set email alerts
|

The levels, prevalence and related factors of compassion fatigue among oncology nurses: a systematic review and meta‐analysis

Abstract: Background Compassion fatigue is described as the phenomenon of exhaustion and dysfunction in healthcare workers resulting from prolonged exposure to work‐related stress and compassion stress. Oncology nurses are at high risk for compassion fatigue. Aims Our study aims to estimate the levels, prevalence and related factors of compassion fatigue dimension in oncology nurses. Design Systematic review and meta‐analysis. Method Ten electronic databases were conducted in the systematic review and meta‐analysis. Tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
33
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 59 publications
10
33
3
Order By: Relevance
“…As nurses' age and years of work experience increased, their risk of experiencing CF decreased. This result supports findings from a vast number of studies during the pre-pandemic period in which nurses' age and years of nursing experience were strongly linked to CF ( Alharbi et al, 2020a , Alharbi et al, 2020b , Alharbi et al, 2020c ; Sacco, Ciurzynski, Harvey, & Ingersoll, 2015 ; Xie et al, 2021 ). For instance, an integrative review by Alharbi et al (2019) found that younger nurses experienced a higher level of CF than older nurses, while cross-sectional studies in China, Korea, the US, and Saudi Arabia identified age and work experience as important risk factors for CF ( Alharbi et al, 2020a , Alharbi et al, 2020b , Alharbi et al, 2020c ; Sacco et al, 2015 ; Xie et al, 2021 ).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…As nurses' age and years of work experience increased, their risk of experiencing CF decreased. This result supports findings from a vast number of studies during the pre-pandemic period in which nurses' age and years of nursing experience were strongly linked to CF ( Alharbi et al, 2020a , Alharbi et al, 2020b , Alharbi et al, 2020c ; Sacco, Ciurzynski, Harvey, & Ingersoll, 2015 ; Xie et al, 2021 ). For instance, an integrative review by Alharbi et al (2019) found that younger nurses experienced a higher level of CF than older nurses, while cross-sectional studies in China, Korea, the US, and Saudi Arabia identified age and work experience as important risk factors for CF ( Alharbi et al, 2020a , Alharbi et al, 2020b , Alharbi et al, 2020c ; Sacco et al, 2015 ; Xie et al, 2021 ).…”
Section: Discussionsupporting
confidence: 86%
“…Prior to the pandemic, the prevalence of CF in nurses ranged from 22% to 60% ( Ortega-Campos et al, 2020 ; Xie et al, 2021 ), while during the initial surge of the coronavirus crisis, the prevalence reached 70% ( Erkin et al, 2021 ). In the current study, 38.6% of frontline nurses experienced medium to high CF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies show that the prevalence of compassion fatigue in nurses ranges from 21.6% to 44.8% depending on the area to which they are assigned such as emergency and ecology [ 1 ]. A systematic review involving 6533 nurses across six different countries showed that 24.48% of the respondents had high levels of compassion fatigue [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of compassion fatigue has been linked majorly to personal factors like gender, and working experience [ 18 , 24 , 25 ]. Organizational risk factors linked to compassion fatigue include work overload, low remunerations, unsupportive peers, lack of control, and ineffective supervision [ 18 ]. Other factors include coping strategy, self-compassion, social support, and professional cognition [ 18 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%